Choice Between Composite and Amalgam Restorations According to Dentists and Patients Perception - Hanan Nahel Mahmood; Asaad Mohammed Abd-alqader; Raya jasm Al-Naimi (University of Mosul, College of Dentistry, 2020)
Aims : The aim of the current study was to evaluate dentists and patients choices of type of restorative materials applied in fillings and their knowledge about the mercury content in amalgam restorations. Methods: a cross sectional descriptive study based on two types of questionnaire, one for the dentists(119) and the other specific for the patients (500) were distributed to determine the knowledge and awareness, preference of amalgam and composite restorations. Results: showed that the of awareness of the dentists about the amalgam controversy came from different sources, half of the dentists sample stated amalgam restorations were safe, were as 21% stated it unsafe. Placement of the selected restoration(either type) was influenced by different factors, recall appointments of patients complaining from several complaint was mostly from composite. For patients 67.6 % didn't have any knowledge about harmful effect of mercury release from amalgam with the majority of the patients stating that they preferred composite or a tooth colored restoration. Conclusion: with in the limitations of this study awareness of safety of dental amalgam among the dentists was low, with a large agreement that postoperative complications were mainly due to composite restorations. For the patients the majority did not know anything about issues related to the mercury content of the amalgam and majority of them favored the placement of composite restoration similar to the color of their teeth.